The effects of hydrochloric acid and glucose supplementation in the drinking water of laying hens on the performance and quality of eggs - Nor Lilawati Mohd. Razali.
An experiment was carried out to study the effect of hydrochloric acid and glucose supplementation in the drinking water, on egg production and quality. A total of 18 commercial layers aged 20 week old are placed in 18 individual cages of the same size. The layers are then divided into 3 separate groups for 3 different treatments. Treatment 1 is given ordinary water, as a control group. Treatment 2 is a mixture of ordinary water with 50% concentration hydrochloric acid, to produce a pH of 4 in the drinking water. For treatment 3, 21 g of glucose is diluted with 300 ml of water to produce a glucose rich drinking water. Feed and water are provided ad libitum. Data such as feed and drinking water intake and energy intake, as well as egg production and quality will be used to determine the effectiveness of the treatments. It was concluded that effects of hydrochloric acid on the feed and drinking water intake, but also on the performance and quality of the eggs. However, glucose supplementation, on the other hand, did not effect performance and quality, but effected the feed and drinking water intake as well as the energy intake/level.